Development of Guided Inquiry-Oriented Student Activity Sheets to Train Metacognitive Skills on the Material of Reaction Rate - Meni Feronika Tainmeta; Harun Nasrudin; Nurina Rizka Ramadhania (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
This study developed a guided inquiry-oriented student activity sheet to train metacognitive skills on reaction rate material. The background shows low metacognitive skills and students' difficulties in understanding the material. The method used was the Borg and Gall R&D model up to the product trial stage, with 30 students of grades XI-8 of Gedangan High School as subjects. The results showed that the developed student activity sheet was valid, practical, and effective. Content and construct validity were classified as very valid and valid, practicality was seen from student responses reaching 90.9%, and relevant activities were more than 91%. Effectiveness was seen from the increase in the N-Gain score (0.55–0.90) and the results of the paired sample t-test were significant (Sig. 0.000). The metacognitive inventory questionnaire also showed very good results. Thus, this activity sheet is suitable for training metacognitive skills in learning reaction rates.